Uniform light-cone gauge for strings in AdS(5) x s**5: Solving SU(1|1) sector. - FROLOV, SERGEY (My University, 2006)
We introduce a uniform light-cone gauge for strings propagating in AdS5 ?S5 space-time. We use the gauge to analyze strings from the su(1|1) sector, and show that the reduced model is described by a quadratic action for two complex fermions. Thus, the uniform light-cone gauge allows us to solve the model exactly. We analyze the near BMN spectrum of states from the su(1|1) sector and show that it correctly reproduces the 1/J corrections. We also compute the spectrum in the strong coupling limit, and derive the famous ?1/4 asymptotics. We then show that the same string spectrum can be also derived by solving Bethe ansatz type equations, and discuss their relation to the quantum string Bethe ansatz for the su(1|1) sector.
PUBLISHED
Keywords: Mathematics; string theory